From the Camps to the Campus: Refugees’ Narratives of Resilience and Multicultural Inclusion in Higher Education - Zoe Karanikola; Foteini Daratzi (Dinamika Ilmu, 2024)
This study explores the experiences of eight refugee students in higher education, specifically in a private American college in Greece. A qualitative narrative approach was used to understand the students’ personal stories through in-depth semi-structured interviews. The data were examined through thematic analysis, which generated several central themes, including stability and citizenship, financial and language barriers, racism, bias and discrimination, and feelings of belonging or exclusion. The findings show that refugee students’ participation in higher education was shaped by legal uncertainty, limited financial resources, language demands, missing academic documents, and the emotional burden of displacement. At the same time, their narratives revealed strong resilience, self-determination, and hope, as higher education helped them rebuild a sense of identity, imagine better futures, and position themselves as potential contributors to their families and communities. Therefore, this study does not only highlight the difficult route from forced migration to academic participation, but also challenges deficit views of refugees by showing their agency, strength, and capacity to learn, adapt, and transform their lives through education.